OKULÖNCESİ ÇOCUKLARININ TÜRKÇE EDİNİMİNDE YAPTIKLARI KURALLAŞTIRMA HATALARININ İNCELENMESİ. - KABADAYI, Abdülkadir (Electronic Turkish Studies)
Language, which is the most important element of social and emotional communication, is a complex communicative tool in which desired symbols with unlimited units are used. While attaining communication and interaction effectively it is inevitable for the children to make mistakes in respect of phonology, morphology and syntax due to the developmental period of the children in question. This study is conducted to analyze the over regularization mistakes preschoolers have made in the process of mother tongue acquisition. 36 preschoolers attending to Fevzi Çakmak Preschool in Karatay Konya are chosen randomly for this study. In this study, the question of what elements of grammar rules of Turkish language the preschoolers overregularize most is tried to be responded. The participants in this study have been observed for 12 weeks longitudinally. The over regularization mistakes the preschoolers made has been recorded by the researcher. It is found out that the participants have made overregularization in the suffixes that make nouns from nouns, nouns from verbs, and the suffixes of intorragations, possesive adjectives, declaration and cogitation moods, time complements of the sentences and numerical concepts in Turkish gramer. Later, the overregularization in question is classified under the title of inflectional, derivational and time complements themes and sub-themes in Turkish. At a last remark, some recommendations are made both to the preschool teachers and parents about how to overcome overregularizational errors the preschoolars made.